Chris Masters address at the National Press Club, Canberra on 9 March 1992 - Masters, Chris; National Press Club (Australia) (1992)
Address given by Chris Masters, investigative journalist at the launch of his book "Inside story". Describes Australian corruption culture, especially in the police force, and the role of journalists in exposing this. Also describes the motives and culture of the media in Australia, the process of 'investigative journalism', the effect of defamation laws on reporting and the perception of bias in the media.
Photographs available.
Also available online
Transcript unavailable.
Keywords: Masters, Chris; Police corruption -- Australia; Journalism -- Australia